Enhancing emission reductions in South African agriculture: The crucial role of carbon credits in incentivizing climate-smart farming practices - L. Hayo; H. Hasegawa (Sustainable Futures)
Agriculture faces environmental threats caused by climate change, exacerbated by greenhouse gas emissions (GHG). As a result, climate change is a pressing issue for agriculture, necessitating strategies like carbon credits to mitigate emissions and enhance productivity. Carbon credits are recognized as a prominent avenue for reducing emissions, as highlighted in the 2023 Climate Change Conference (COP28). However, research on carbon credit targeting non-CO2 emissions from agriculture is limited. Thus, this study employed stochastic frontier analysis (SFA) to examine panel data from 1991 to 2020, focusing on the effectiveness of climate-smart agriculture in reducing South African agricultural GHG emissions. The data included non-mechanical agricultural emissions sources, paying attention to emissions from crops and livestock. The findings supported the hypothesis, suggesting that increasing incentives, specifically carbon credits, can raise agricultural productivity while reducing emissions. The study also found that inefficiencies in agriculture significantly impact farm output and emissions. The results indicate that offering GHG carbon credits for agriculture promotes sustainable practices, as methane and nitrous oxide emissions are short-lived and can help reduce climate change impact through carbon sequestration. Prioritizing on-farm emissions, soil fertility improvement, reduced fertilizer use, and better livestock management can lead to positive change through climate-smart farming practices. Therefore, promoting customized GHG credits for agriculture mechanisms can lead to positive change through climate-smart farming practices. Thus, it is necessary to enhance mitigation strategies, policies, and farm practices. Finally, the study emphasizes the significance of evidence-based GHG credits for agriculture mechanisms policies and the need for future research into ways to persuade farmers to participate in the carbon credit market.